The Effects of Hydroalcoholic Extract from Alhagi on Matrix Metalloproteinase-9 Production in Peripheral Blood Mononuclear Cells from Patients with Rheumatoid Arthritis - Ahmadi, Mahbouba; Ebrahimi, Reyhane; Ansari, Mohammad; Akhlaghi, Masoumeh; Mahmoudi, Mahdi; Amin, Gholamreza; Emamgholipour, Solaleh (Natural Products Journal, The, 2020)
Background: The up-regulation of matrix metalloproteinase 9 (MMP-9) along with the imbalanced ratio of MMP-9 to tissue inhibitor of metalloproteinase 1 (TIMP-1) is important in the pathogenesis of Rheumatoid Arthritis (RA). Here, we investigated whether hydroalcoholic extract from the root of Alhagi camelorum Fisch can affect the levels of MMP-9 and TIMP-1 in peripheral blood mononuclear cells (PBMCs) of RA patients. Objective: In the current study, we suggest that Alhagi may have an inhibitory effect on MMP-9 production, which is mainly responsible for joint destruction in RA. In addition, we would like to stress that our findings, along with others, can provide the basis for future studies, which might help in determining the role of chemical ingredients of Alhagi as therapeutic targets for RA treatment. Methods: PBMCs were isolated from 12 RA patients and 12 healthy subjects and treated with two concentrations of Alhagi extract (100 and 500 μg/ml) for 24 h. MMP-9 gene expression and protein production, TIMP-1 levels and nitric oxide (NO) production were evaluated using standard methods. Results: Alhagi (500 μg/ml) caused a significant reduction in the expression and activity of MMP-9 in PBMCs from healthy (p=0.003 for both of them) and patient (p= 0.05 and p=0.02 respectively) subjects. Moreover, Alhagi (100 μg/ml) decreased MMP-9 production in the healthy subjects’ group (p=0.02). Conclusion: The present study reveals the inhibitory effects of Alhagi on the production of MMP-9 as the main responsible cause of joint destruction in RA.
Keywords: Matrix Metalloproteinase 9 (MMP-9)